Tantangan Transformasi Digital Bagi Budaya Dan Potensi Daerah “ Cakap Tips Dan Trik Membuat Konten Promosi Wisata” - kadek riyan putra richadinata riyan (Jurnal Pengabdian kepada Masyarakat Nusantara, 2022)
Digital Transformation is here to change people's views on travel. The presence and progress of this technology requires the community to actively participate in developing Tourism Villages using technology. The presence of social media in the world of tourism makes it very easy for tourists to get complete information about lodging, entrance prices for a tourist attraction, transportation, as well as culinary and entertainment that can be enjoyed. The presence of digital promotions makes changes to make it easier for tourists to visit both foreign and domestic to obtain information. The method used in this service program is carried out in several sequences including: compiling health protocols for community service, conducting site surveys and analyzing problems and arranging meetings with village officials and presentation of the material presented. The activities carried out provide education and training for Cakap Tips and Tricks for Creating Tourism Promotion Content, creating content through this digital platform can make it easier for traditional village communities to promote tourist attractions in the local traditional village.